The Influence of Point of Purchase, Brand Image and Increasing Turnover of Mutouch Product Sales in Yogya Riau Junction - Wala Erpurini; Hakim Mulfatama; Restu Astuti (Institute of Computer Science (IOCS), 2022)
This research aims to determine the effect of point of purchase and brand image on increasing sales turnover of Mutouch products in Yogya riau junction, the population in this study is consumers who shop for products in yogya riau junction, respondents in this study were 80 people, this research method uses the descriptive and associative research, which examines the effect between the independent variables and the dependent variable. The results of the research through descriptive analysis show that point of purchase and brand image on increasing sales turnover of Mutouch products in Yogya Riau Junction are in a fairly good category, the data analysis technique used is path analysis, associative testing shows the effect of point of purchase on turnover by 27, 33%, the influence of brand image on turnover by 29.6%, the effect of point of purchase and brand image on increasing sales turnover of Mutouch products in Yogya Riau Junction by 57,0%